The Effect of Tax, General Allocation Fund, and Retribution on Regional Expenditure - Wasil, Mohammad (LPPM of NAROTAMA UNIVERSITY, 2024)
Regional autonomy gives local governments the authority to manage their finances, including regional expenditure, in order to achieve national goals. Effective and efficient regional spending is the key to regional development and improving community welfare. This study aims to analyze the effect of local taxes, local levies, the General Allocation Fund (DAU), and the Special Allocation Fund (DAK) on regional expenditure in Central Java and Yogyakarta. This study uses secondary data in the form of Budget Realization Reports (LRA) in 2019 and 2020. Data analysis was performed with multiple linear regression, F test, t test, and coefficient of determination. The results showed that local taxes, DAU, and DAK have a positive and significant influence on local spending. Local retribution has no effect on local expenditure. The conclusion is that local governments need to maximize local revenue, especially local taxes, and optimize the use of DAU and DAK to increase the effectiveness and efficiency of local spending